Safety and Efficacy of Magnetic Resonance–Guided Vacuum-Assisted Large-Volume Breast Biopsy (MR-Guided VALB). Issue 3 (March 2017) - Schrading, Simone; Strobel, Kevin; Keulers, Annika; Dirrichs, Timm; Kuhl, Christiane K.
Abstract : Objective: Magnetic resonance (MR)-guided vacuum-biopsy is technically demanding and may fail depending on target-lesion size or breast size, and location of lesions within the breast. We developed an MR-guided vacuum-assisted biopsy protocol that collects larger amounts of tissue, aiming at an at least partial or complete ablation of the target-lesion, just as it is intended during surgical (excisional) biopsy. Rationale is to avoid biopsy failures (false-negative results due to undersampling) by collecting larger amounts of tissue. We report on our experience with MR-guided vacuum-assisted large-volume breast biopsy (VALB) (MR-guided VALB) with regard to clinical success and complication rates. Materials: Institutional review board–approved analysis of 865 patients with 1414 MR imaging (MRI)-only breast lesions who underwent tissue sampling under MRI guidance. Magnetic resonance–guided VALB was performed on a 1.5 T-system with a 9G system. Per target lesion, we collected at least 24 samples, with the biopsy notch directed toward the position of the target until on postbiopsy control imaging the target lesion appeared completely or at least greatly removed. The standard-of-reference was established by at least 24-months follow-up (for benign biopsy results), or results of surgical histology (for malignant or borderline results). We investigated the technical success rates as a function of factors that usually interfere with MR-guided vacuum biopsy. Results: Target lesions were located in the central versus peripheral parts of the breast in 66.6% (941/1414) versus 33.6% (473/1414), occurred in large, intermediate, or small breasts in 22.7% (321/1414), 56.4% (797/1414), or 20.9% (296/1414), corresponded to nonmass enhancement (NME) versus mass enhancement (ME) in 64.0% (905/1414) vs. 36.0% (509/1414), with an average size of 23 mm for NME versus 9 mm for ME, respectively. Primary technical failures, that is, inability to reach the target lesion occurred in 0.2% of patients (2/865) and 0.1% of target lesions (2/1414). Successful biopsy, that is, an MR-guided VALB diagnosis matching with the standard of reference, was achieved in 99.5% (859/863) of patients and 99.7% (1408/1412) target lesions that had been amenable to MR-guided VALB. In 0.5% of patients (4/863) and 0.3% of target lesions (4/1412), a radiologic-pathologic mismatch suggested a false-negative biopsy, confirmed by secondary excisional biopsy. The likelihood of failure was independent of the lesion's location in the breast, breast size, target lesion size, or target lesion type (NME vs ME). None of the patients with benign MR-guided VALB diagnoses developed breast cancer at the biopsy site during follow-up of 2 years. None of the patients developed major complications. Conclusion: Magnetic resonance–guided VALB is a safe procedure that is associated with a high success rate (99.7%) that is independent of the size, type, or location of a target lesion, or the size of the breast, and is associated with a very low complication rate.